FACTORES DE RIESGO PSICOSOCIALES RELACIONADOS CON LAS CAUSALES DE PRIVACIÓN DE LA PATRIA POTESTAD (2016)
At present, the family institution gives a central role to explain from different disciplines individual and group behavior in internal and external environments called core family related to the society as such, where psychosocial risk factors taking important part triggered in matters relating to the grounds for deprivation of parental rights, because the legal standard that supports in Colombia, which has been significantly transformed the protective regime of children and adolescents. This systematic transfigured patriarchal orientation that had custody at the source.At the same time particular emphasis to experienced changes associated with social disintegration, arising from the degradation of the social core due to dysfunctional families, added to this is done, is part abandonment of the child by the father as a result the lack of: fear of assuming the role of father at an early age and economic resources, responsibility, in addition to other crisis factors that according to a study conducted in 47 nations, Colombia is the country where people marry less, just half of households have both parents and 40 percent of children and adolescents living with people other than his family.